2018
DOI: 10.1016/j.nbt.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Laccase catalyzed elimination of morphine from aqueous systems

Abstract: Pharmaceuticals contaminate the environment for several reasons, including metabolic excretion after intake, industrial waste and improper disposal. The narcotic drug morphine is commonly utilized for chronic pain management, and the distribution of morphine in aqueous systems and in waste waters is of high concern. Here, the removal of morphine by a laccase from Myceliophthora thermophila both in its free form as well as immobilized on Accurel MP1000 beads was investigated. Complete morphine elimination was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In recent years, Pellis et al prepared the immobilized laccase using Accurel MP1000 beads as a carrier to facilitate the oxidation of Kraft lignin (KL) and lignosulfonate (LS) [16]. Greimel et al used immobilized laccase to remove morphine and complete morphine elimination was achieved within 30 min [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Pellis et al prepared the immobilized laccase using Accurel MP1000 beads as a carrier to facilitate the oxidation of Kraft lignin (KL) and lignosulfonate (LS) [16]. Greimel et al used immobilized laccase to remove morphine and complete morphine elimination was achieved within 30 min [17].…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, one of the applications of laccase is the detection of various compounds in certain foods. However, it is also used for the synthesis of chemical compounds, their detection and recently it has been reported that the enzyme is capable of removing morphine from aqueous systems (Huber et al, 2018). This reflects the great potential of the enzyme not only in the food industry but also for the recovery of contaminated areas, hence the importance and relevance of the information presented here.…”
Section: Potential Trends and Current Challengesmentioning
confidence: 62%
“…Each of the dried LS samples was resuspended in ultrapure water at 20 wt % and left for stirring at 40 °C until completely solubilized, followed with a NaOH addition to reach pH 7 (pH at which MtL shows the highest catalytic activity). 11 Enzymatic oxidation was carried out in 500 mL transparent durum bottles with tight-fitting tube holes on the lid to allow the air supply. The reaction was started by introducing 233 nkat/mL laccase and was continuously supplied with 10 cm 3 /min oxygen at 37.5 °C while mixing under vigorous stirring at 900 rpm.…”
Section: Materials and Methodsmentioning
confidence: 99%